Strategi Pemasaran Syariah Dalam Meningkatkan Penjualan Produk Hijab Di Toko Vivi Jilbab Jambi - Anjani, Sonali Dwi Sari; Rafidah, Rafidah; Lubis, Puteri Anggi (Program Studi Manajemen Keuangan Syariah, 2025)
This study aims to analyze sharia marketing strategies in increasing hijab product sales at Toko Vivi Jilbab Jambi by examining the implementation of Islamic principles in marketing practices and the challenges faced. The research uses a qualitative approach with a descriptive case study design. The study was conducted at Toko Vivi Jilbab Jambi, located on Jl. Kol. Amir Hamzah, Telanaipura District, Jambi City. Data were collected through passive observation, in-depth interviews with the shop owner and employees, and documentation. Research instruments included semi-structured interview guides, field notes, and visual documentation tools. Data analysis employed the Miles and Huberman model, consisting of three stages: data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of sources, techniques, and time. The results indicate that Toko Vivi Jilbab Jambi has fully implemented the 7P sharia marketing mix, including halal products, fair pricing, strategic location, honest promotion, friendly and trustworthy service, transactions conducted in accordance with Islamic law, and a clean and Islamic-compliant physical environment. Additionally, the shop’s trading practices reflect the traits of Prophet Muhammad (PBUH), such as shidiq (truthfulness), amanah (trustworthiness), tabligh (communicativeness), and fathanah (wisdom). Internal challenges include the rapid change of hijab trends, while external challenges involve increasingly intense market competition. This study contributes to the development of Islamic marketing knowledge and serves as a reference for similar businesses. Future research is recommended to involve broader and more varied settings.